Cell Membrane Camouflaged Hydrophobic Drug Nanoflake Sandwiched with Photosensitizer for Orchestration of Chemo‐Photothermal Combination Therapy. Issue 20 (29th March 2019) - Zhang, Lijun; Zhang, Xiao; Lu, Guihong; Li, Feng; Bao, Weier; Song, Cui; Wei, Wei; Ma, Guanghui
Abstract: Many candidate anticancer drugs have suffered from their intrinsic hydrophobicity, which poses several obstacles for clinical application. To overcome this challenge and further improve the performance, herein a nanocrystal‐based biomimetic formulation with a sandwich structure is developed. As the core, flake shaped nanocrystals (NCs) with high loading of the hydrophobic drug hydroxycamptothecin (HCPT) are synthesized via a mild nanoprecipitation process by exploring the template effect of serum albumin. Meanwhile, the camouflaged cancer cell membrane (CM) composed of plentiful membrane proteins endows the NCs with homotypic targeting capacity at tumor sites. In addition, the photosensitizer indocyanine green sandwiched between NCs and CM not only converts near infrared light to heat for photothermal treatment but also improves the dissolution of HCPT NCs for chemotherapy. These features corporately achieve the orchestration of chemo‐photothermal combination therapy and completely inhibit tumor growth with few adverse effects, showing promise as a new modality for the utilization of hydrophobic drugs to treat cancer. Abstract : A nanocrystal‐based delivery system is developed for orchestration of chemo‐photothermal combination therapy. As the core, a hydrophobic drug nanocrystal with ﬂake shape is camouﬂaged with a cancer cell membrane for homotypic tumor targeting. Meanwhile, the photosensitizer sandwiched between nanocrystal and membrane not only converts infrared light to heat for photothermal treatment but also improves the dissolution of the hydrophobic drug for chemotherapy.